The importance of management by nurses in the sectors of a hospital unit (International Seven Journal of Health Research, 2023)
The nurse in hospital management is becoming a broader area in the midst of nursing, people are becoming more interested in the profession and in the position, in which it is highly disputed. The purpose of the position is to bring improvements to the hospital unit, in assistance, for profit, economic and social purposes. Seeking to bring the organization of the sector worked, promote lectures on adequacy to other nurses so that everyone in the unit has a minimum of knowledge. The objective of this research is to investigate the importance of the nurse manager in a hospital unit in the city of Rio de Janeiro. The study method was chosen qualitative in nature and field research, researching scientific articles and data collection was also carried out from a questionnaire, seeking to acquire information from nursing professionals who work in the field of hospital management, so that they can pass on a little of their knowledge, bringing us the negative and positive points of this position. in the hospital unit. DOI:https://doi.org/10.56238/isevjhv2n2-016